2015
DOI: 10.1186/s40793-015-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

High quality draft genome sequence of Bacteroides barnesiae type strain BL2T (DSM 18169T) from chicken caecum

Abstract: Bacteroides barnesiae Lan et al. 2006 is a species of the genus Bacteroides, which belongs to the family Bacteroidaceae. Strain BL2T is of interest because it was isolated from the gut of a chicken and the growing awareness that the anaerobic microbiota of the caecum is of benefit for the host and may impact poultry farming. The 3,621,509 bp long genome with its 3,059 protein-coding and 97 RNA genes is a part of the Genomic Encyclopedia of Type Strains, Phase I: the one thousand microbial genomes (KMG) project. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…34 They also play an important role against pathogenic microorganisms in the gut microbiota of broiler chickens. 34 Ruminococcaceae members were considered as beneficial autochthonous taxa in the gut microbiota of broilers with strong ability in degradation of diverse polysaccharides and fibers, especially in the cellulose and other highly recalcitrant polysaccharides, then producing organic acids to provide energy for the intestinal epithelium and host. 32,35 Numerous studies demonstrated that the relative abundance of Ruminococcaceae was positively associated with improved growth performance and feed efficiency, as well as intestinal morphology and barrier of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…34 They also play an important role against pathogenic microorganisms in the gut microbiota of broiler chickens. 34 Ruminococcaceae members were considered as beneficial autochthonous taxa in the gut microbiota of broilers with strong ability in degradation of diverse polysaccharides and fibers, especially in the cellulose and other highly recalcitrant polysaccharides, then producing organic acids to provide energy for the intestinal epithelium and host. 32,35 Numerous studies demonstrated that the relative abundance of Ruminococcaceae was positively associated with improved growth performance and feed efficiency, as well as intestinal morphology and barrier of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that our study provides the rst-evidence-in-chickens for the majority (81/125) of these species (Additional File 4, Supplementary Table 3). Examples include: Jeotgalicoccus halophilus, rst isolated from the traditional fermented seafood, Jeotgal [77]; Aliicoccus persicus, rst isolated from a hypersaline lake [78]; and Bacteroides reticulotermitis, rst isolated from the gut of a termite [79]. A search of PubMed with the species name and the terms "humans" and infection" suggests that nearly 40% of these known species have been associated with human infection, highlighting the role of the chicken gut as a source of zoonotic pathogens.…”
Section: Analysis Of Bacterial Metagenomic Species Primarily Using Tmentioning
confidence: 99%
“…This suggested that our study provides the rst-evidence-in-chickens for the majority (81/125) of these species (Table S14). Examples include: Jeotgalicoccus halophilus, rst isolated from the traditional fermented seafood, Jeotgal [77]; Aliicoccus persicus, rst isolated from a hypersaline lake [78]; and Bacteroides reticulotermitis, rst isolated from the gut of a termite [79]..…”
Section: Remarkable Microbial Genome Diversity In the Chicken Gutmentioning
confidence: 99%